Caracterización morfológica floral de la especie silvestre “arbórea” (tibouchina lepidota) en el bosque bsmno3 bosque siempre verde montano de cordillera occidental de Los Andes desde los 2000 – 3000 m.s.n.m sector La Esperanza cantón Pujilí provincia de Cotopaxi 2018 - Espín Bautista, Henry Olivo (2018)
This investigation Project had like a goal to generate the floral characterization morphological analysis of wild species “arbórea” in the forest BsMnO3, the forest is always Green, it’s located in the western mountain rage of Andes from 2000-3000 m.s.n.m. it is in La Esperanza town, for this I have realized some activities like a constant monitoring to the best floral species period in the bioclimatic stage that correspond to the investigation. I used two phases, in the field phase the external morphological characteristics of the flower were analyzed using the established methodology for the collection, conservation and transport of flowers. In the laboratory phase the internal characteristics of the flower were determined, for this it was based on the guide "The flower, inflorescence and fruit", elaborated by Blgo. Richard Javier Huaranca Acostupa (2010). In the species under study, the flowering stage of Tibouchina Lepidota was determined, which occurs in the second week of the month of May and ends the fourth week of July, presenting an inflorescence of Helicoidal Cimosa type, with heteroclamid flowers with a corolla Dialipétala, with five petals. The calyx is gamosépalo with 5 sepals. The androceo consists of five 12 anthers and the gynoecium has an inferior ovary, Bicarpalar, bilocular and Multiovular. According to the Munsell scale the coloring of the flower correspond to the 5RP and 5P codes